2022
DOI: 10.3390/nano12030526
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Elasticity of Flexible Polymer Chains Using Interferometer-Based AFM

Abstract: We estimate the elasticity of single polymer chains using atomic force microscope (AFM)-based oscillatory experiments. An accurate estimate of elasticity using AFM is limited by assumptions in describing the dynamics of an oscillating cantilever. Here, we use a home-built fiber-interferometry-based detection system that allows a simple and universal point-mass description of cantilever oscillations. By oscillating the cantilever base and detecting changes in cantilever oscillations with an interferometer, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This can be ascribed to the increased flexibility of PEG with respect to its chemical structure. 28,29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be ascribed to the increased flexibility of PEG with respect to its chemical structure. 28,29…”
Section: Resultsmentioning
confidence: 99%
“…This can be ascribed to the increased flexibility of PEG with respect to its chemical structure. 28,29 Motivated by the above findings, we also compared the mechanical properties of 1 . PSt and 1 .…”
Section: Effect Of Chemical Structure and Flexibility Of Polymeric Gu...mentioning
confidence: 99%
“…These few monomers are expected to be at the edge of the membrane, where the polymer is forced to be orientated perpendicular to the membrane and the bending stiffness is the largest. Recent research showed that the bending stiffness (persistence length) of PS is 1 monomer, 34 which implies that the rest of the PS monomers are expected to be coiled up. To determine the degree of coiling, Δ χ PS is calculated as a function of the fraction of the maximal extension of PS in the polymersome membrane, assuming that phenyls are free to rotate around the bonds connecting them to the PS backbone (for more details on this calculation see the Supporting Information 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since polymers are composed of repeatedly connected units, they can be fabricated so as to have flexible forms [ 102 , 103 , 104 , 105 ]. In addition, polymers have physical variables that determine their physical properties, and thus each polymer can be used in various ways [ 106 , 107 ].…”
Section: Polymer/metal-hybrid-based Aptamer Sensorsmentioning
confidence: 99%